The Effect of Antibacterial Agent of Pangasius sutchi Bone Extract Against Porphyromonas gingivalis - Muhammad Rizky Pratama; Siti Rusdiana Puspa Dewi; Hema Awalia (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2023)
Introduction: Periodontal disease is the most common dental problem mainly due to bacterial infection. The highest virulence bacteria found in periodontal disease is Porphyromonas gingivalis. Pangasius sutchi bone extract contains bioactive peptides which have the potential effect to inhibit the growth of Gram-negative bacteria such as P. gingivalis. Purpose: This study aimed to determine the effect of an antibacterial agent of Pangasius sutchi bone extract against Porphyromonas gingivalis. Methods: This research was in vitro laboratory experimental study with a post-test-only control group design. The treatment groups consisted of Pangasius sutchi bone extract using concentrations of 10%, 20%, 40%, 60%, and 100%, positive control (cefixime) and negative control (placebo). Results: The results showed that each concentration of Pangasius sutchi bone extract had antibacterial properties. The largest diameter of the inhibitory zone was at 100% concentration. The minimum Bactericidal Concentration (MBC) was at a concentration of 40%, and the Minimum Inhibitory Concentration (MIC) was 20%. Conclusion: Pangasius sutchi bone extract had an antibacterial effect against Porphyromonas gingivalis.